Toxic effects of glyphosate on diploid and triploid fin cell lines from Misgurnus anguillicaudatus. (August 2017) - Qin, Yanjie; Li, Xia; Xiang, Yang; Wu, Di; Bai, Liwen; Li, Zhuangzhuang; Liang, Yan
Abstract: We examined the toxic effects of glyphosate on diploid (DIMF) and triploid (TRMF) fin cell lines from the Oriental Weather Loach Misgurnus anguillicaudatus . The LC50 values of glyphosate estimated by methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay were 315.34 and 371.77 mg/L for DIMF and TRMF, respectively. Superoxide dismutase (SOD) and glutathione-S-transferase (GST) activities in DIMF and TRMF cells gradually increased and then decreased with increasing glyphosate concentrations, reaching a maximum at 240 mg/L glyphosate. In contrast, acetylcholinesterase (AChE) activities in DIMF and TRMF decreased with increasing concentrations of glyphosate in a concentration-dependent manner. SOD and AChE activities were generally significantly higher in TRMF compared with DIMF cells (P < 0.05). The rates of micronucleus and abnormal nuclei were significantly higher in DIMF and TRMF groups treated with 80–560 mg/L glyphosate compared with the control groups (P < 0.01). The highest micronuclei rates in both DIMF and TRMF cells (both 4.30‰) occurred at 400 mg/L glyphosate. There were no differences in the rates of micronuclei and abnormal nuclei between DIMF and TRMF cells at any glyphosate concentration. Cell damage, including chromatin condensation, nucleus distortion, and broken and reduced endoplasmic reticulum, mitochondria, and ribosomes, were found in both cells treated with the LC50 concentration of glyphosate. Moreover, vacuolization and apoptotic bodies occurred in glyphosate-exposed DIMF and TRMF cells, indicating apoptosis. These results indicate that glyphosate in the range of tested concentrations represent a potential risk to loach through inhibiting proliferation of diploid and triploid cell lines and induces micronuclei and apoptosis. Highlights: We examined toxic effects of glyphosate on diploid and triploid loach cell lines. The LC50 of glyphosate were 315.34 and 371.77 mg/L for diploid and triploid cells. Glyphosate stimulated antioxidant defenses, inhibited AChE activities in both cells. Glyphosate inhibits proliferation, induces micronuclei and apoptosis in both cells.